Business Process Analysis and Information System Design to Support IT Governance Practices in Construction Services - novara; Intan Azizah (Governance IT Adoption and Technology Advance, 2026)
This study aims to analyze system requirements and design a web-based company profile information system to support the effectiveness of IT governance in a construction services organization. This study occurred due to the lack of a structured and integrated information system, which led to inefficient information delivery and limited accessibility for stakeholders. A qualitative approach was used through observation and interviews to identify system requirements and analyze existing business processes. Business process modeling was performed using Business Process Model and Notation (BPMN) to describe the current (as-is) and proposed (to-be) processes. Next, the system design was developed using Unified Modeling Language (UML), including Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams to provide a structured overview of the system. The database was designed using Entity Relationship Diagrams (ERD) to ensure structured and integrated data management. The system design provides a structured overview to manage and convey company information more efficiently. Data in the system is managed by the administrator and accessed dynamically by users. In addition, this design supports the principles of IT governance by ensuring alignment between business processes and information technology, improving data management, and increasing transparency and control. This study concludes that the designed system can improve the effectiveness of information management and contribute to better IT governance. Further research is recommended to implement and evaluate this system in a real-world environment